(untitled) (Journal of Political Science and International Relationship, 2025)
After the Taliban returned to power in 2021, the United Nations launched a process called the “UN-led Doha Process” to improve the human rights situation and resolve Afghanistan’s problems. This process, which included three international meetings in Qatar attended by 25 countries and five international organizations, did not yield positive results despite the Taliban’s efforts and invitation to the third meeting, and even the human rights situation, especially the rights of women and girls, worsened. In contrast, the Taliban’s political and military opponents launched another process called the “Vienna Process” in Austria, which has held five meetings so far and has succeeded in creating relative cohesion among these groups. However, the United Nations and countries involved in Afghan affairs have not supported this process. This study examines and compares the UN-led Doha Process and the Vienna Process initiated by the Austrian Institute for International Affairs and analyzes the strengths and weaknesses of both processes. The results of this study can help to better understand the reasons for the failure of the Doha Process and the lack of support for the Vienna Process, and provide suggestions for improving international efforts to resolve the Afghan crisis.